Work Program Analysis Guiding Training in Candirejo Tourism Village, Borobudur District, Magelang Regency - Nurul Azizah, Fatimah; Khairune Nisa, An Nuur; Oktaviani Gustiarti, Putrisari; Dava Putri Widodo, Sabrina (Ann Publisher, 2023)
Indonesian tourism has become a significant non-oil and gas sector in the country's foreign exchange contribution. This article explores the development of Candirejo Tourism Village as a clean, beautiful, safe, and comfortable tourist destination with the preservation of nature and maintained traditional values. The village has attractions, accessibility, and amenities that support the tourist experience. This study used a qualitative approach to observe and analyze residents' participation levels in language training programs and experience-sharing sessions. The data was collected by attending a training activity held on November 13, 2022, at the Candirejo Village Hall Office. Respondents involved administrators and village tourism actors, with 25 people. This research focuses on Candirejo Village's role in developing human resources (HR) through French and English Guidance Training programs and Sharing Sessions on Strengthening the Role of Tourism Managers.